Factors Affecting Company Value In The Consumer Noncyclical Industry Sector Listed On The Indonesia Stock Exchange (IDX) - Lusi Nursela; Melina Siswani; Erwin Budianto (Publikasi Indonesia, 2024)
Company value is a measure of the success of a company on its operational activities. This study aims to determine the factors that can affect the value of companies in the Consumer Non-Cyclical industrial sector listed on the Indonesia Stock Exchange (IDX). By using the perposive sampling method to determine the number of research data samples obtained by 66 companies. The data were analyzed using the classic Moderated Regression Asset (MRA) assumption test with SPSS version 25 for windows. The results of this study show that Return On Asset (ROA) affects company value, while Total Asset Turnover (TATO) does not affect company value, but Return On Asset (ROA) and Total Asset Turnover (TATO) simultaneously affect company value in the Consumer Non Cyclical industry sector. The conclusion is Return On Assets (ROA) has a partial effect on company value (PBV) in non-cyclical consumer sector companies listed on the IDX in 2020-2022 or ho rejected and ha accepted.